Phase II trial of panobinostat, an oral pan‐deacetylase inhibitor in patients with primary myelofibrosis, post–essential thrombocythaemia, and post–polycythaemia vera myelofibrosis. (23rd May 2013) - DeAngelo, Daniel J.; Mesa, Ruben A.; Fiskus, Warren; Tefferi, Ayalew; Paley, Carole; Wadleigh, Martha; Ritchie, Ellen K.; Snyder, David S.; Begna, Kebede; Ganguly, Siddhartha; Ondovik, Michael S.; Rine, Jessica; et al.
Summary: Myelofibrosis (MF) is a Philadelphia chromosome–negative stem cell myeloproliferative neoplasm (MPN) associated with cytopenias, splenomegaly, constitutional symptoms, and poor prognosis. MF patients commonly express JAK2 V617F mutation and activation of Janus kinase (JAK)/signal transducer and activator of transcription (STAT) signalling. Agents targeting the JAK/STAT pathway have demonstrated efficacy in patients with MF. This study evaluated panobinostat, a pan‐deacetylase inhibitor that depletes JAK2 V617F levels and JAK/STAT signalling in MPN cells, in patients with primary MF, post–essential thrombocythaemia MF, and post–polycythaemia vera MF. Patients received panobinostat 40 mg administered three times per week. Dose reductions were permitted for toxicities. The primary endpoint was response rate at 6 months using International Working Group for Myelofibrosis Research and Treatment (IWG‐MRT) consensus criteria. Analyses of peripheral blood cells from treated patients revealed that panobinostat inhibited JAK/STAT signalling, decreased inflammatory cytokine levels, and decreased JAK2 V617F allelic burden. However, panobinostat was poorly tolerated at the dose and schedule evaluated, and only 16 of 35 patients completed ≥2 cycles of treatment. One patient (3%) achieved an IWG‐MRT response. Common adverse events were thrombocytopenia (71·4%) and diarrhoea (80·0%). Although molecular correlative analyses suggested that panobinostat inhibits key intracellular targets, limited clinical activity was observed because of poor tolerance.